Can vegetation corridors support a small mammal community similar to that found within forest fragments? A case study in southeastern Brazil. (2nd January 2017) - Fialho, Mariana Y. G.; Cerboncini, Ricardo A. S.; Passamani, Marcelo
ABSTRACT: Vegetation corridors are generally proposed as a strategy to reduce forest fragment isolation in fragmented landscapes. In southern Minas Gerais, Brazil, vegetation corridors emerged naturally after native trees colonized excavations used as boundaries by farm owners in the eighteenth century. We tested the use of these structures by small mammals and compared diversity among corridors and forest fragments. Community richness and abundance were similar in corridors and forest fragments, and we identified movements of small mammals between corridors and forest fragments. We suggest that governmental policies should encourage farm owners to conserve vegetation corridors, especially in this fragmented landscape.